Wildlife management on communal land in Namibia - Forslund, Johanna (2007)
In this paper the anti-poaching effects achieved under the actual implementation of the economically-based system for management and utilization of wildlife (Community Based Natural Resource Management, CBNRM) initiated in Namibia in 1995, is theoretically contrasted to the intended policy design. By contrasting a Nash equilibrium, where the park agency and the local community act like competitors rather than companions, to a collusive equilibrium, where the two actors work together as a united entity, more local anti-poaching activities is found in the latter case. Negative externalities, such as illegal hunting, could be understood as better internalized and, thus, a more preferable economically-based system for the management and utilization of wildlife appears. Despite great success in terms of increased wildlife number following the economic incentive approach, the model implications suggest conservation incentives to be even better realized if the implemented CBNRM policy in Namibia could re-establish the intended policy design. That is not to be understood as criticim of the approach as such. Rather it should be viewd as a contribution for further development and success.